Evolusi Pemerolehan Bahasa: Analisis Hakikat, Faktor Pendukung, dan Peran Organ Bicara dalam Era Digital - Salimatul Hairo; Tatu Putri; Madona Safitri; Silvina Noviyanti (STKIP Subang, 2025)
Language acquisition is a natural yet complex process influenced by the interaction of biological factors, the environment, and communication experiences. Amid the increasingly digital age, patterns of language acquisition in children show significant shifts, ranging from language input to speech organ performance. This journal analyzes the nature of language acquisition, major theories such as behaviorism, nativism, and interactionism, as well as supporting factors like linguistic environment, social interaction, and biological readiness. Additionally, this journal examines language development over time and the involvement of body organs such as the brain, tongue, vocal cords, and respiratory system. With a critical approach, this paper questions the adequacy of old theories in explaining new phenomena, particularly among generations growing up with digital media. Findings indicate that language acquisition is now hybrid, a combination of natural and digital input, which impacts in phonological, lexical, and pragmatic variations.